2017
DOI: 10.4103/ua.ua_43_17
|View full text |Cite
|
Sign up to set email alerts
|

The role of the endothelin axis in promoting epithelial to mesenchymal transition and lymph node metastasis in prostate adenocarcinoma

Abstract: Introduction:Aberrant activation of endothelin (ET) axis has been identified as a key player in tumor growth and metastasis in several tumor types. However, little is known about the possible interaction of the ET with epithelial to mesenchymal transition (EMT), a process that transforms tumor cells in a motile, resistant to apoptosis phenotype prone to invasion and metastasis. The aim of this study was to investigate the activation of the ET axis in prostate adenocarcinoma and examine possible associations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Endothelin signaling is involved in a number of processes related to tumor growth and its progression, including cell survival, invasion, and metastasis (Bagnato et al 2008 ). Papanikolaou et al ( 2017 ) demonstrated EDN1 and EDNRA overexpression in prostate cancer which correlated with SNAIL activity, indicating possible EMT induction via the endothelin pathway. Similar conclusions were also drawn in the case of endometrial cancer (Czerwiński et al 2021 ), where EDN1 and EDNRA levels were elevated, which is consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelin signaling is involved in a number of processes related to tumor growth and its progression, including cell survival, invasion, and metastasis (Bagnato et al 2008 ). Papanikolaou et al ( 2017 ) demonstrated EDN1 and EDNRA overexpression in prostate cancer which correlated with SNAIL activity, indicating possible EMT induction via the endothelin pathway. Similar conclusions were also drawn in the case of endometrial cancer (Czerwiński et al 2021 ), where EDN1 and EDNRA levels were elevated, which is consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that low GS samples exhibited higher ET A R expression compared with intermediate GS samples, indicating that in primary tumors from patients without treatment, the expression levels of ET A R were decreased and may be associated with the progression of PCa. Upregulation of ET A R and ET-1 expression has been demonstrated in the early stages of PCa ( 16 ) and higher expression levels of ET A R and ET-1 are associated with advanced tumor stage ( 25 ). Furthermore, androgen-sensitive cells (LNCaP) cultured in androgen-deprived medium for 5 months have been indicated to exhibit increased levels of ET A R and ET-1 mRNA, suggesting that this axis may serve an important role in the progression of PCa to CRPC ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we aim to define how the signaling transduced by ET-1/ET-1R axis stands at the centerpiece of a signaling hub shared by tumor and stromal cells, expanding aspects that are critical for tumor growth and metastatic progression. Such feature may be attributable to the ET-1 axis ability to intercept other signaling pathways, realizing an intricate network that modulates multiple steps related to cancer metastatization [ 5 , 51 53 ]. Downstream of ET-1R, β-arr1 has now become a reference node able to engage multiple signal transducers from different cell compartments and with various functions, in turn, directing the integration of ET-1R signaling with other pathways.…”
Section: The Et-1-driven Signaling Network In Tumor Cells and Tumor‐mmentioning
confidence: 99%
“…Downstream of ET-1R, β-arr1 has now become a reference node able to engage multiple signal transducers from different cell compartments and with various functions, in turn, directing the integration of ET-1R signaling with other pathways. Among the ET-1R/β-arr1-directed functions rank the cell attitude to switch from an epithelial to a mesenchymal phenotype (EMT), that fuels tumor cell migration, invasion and therapy resistance [ 33 , 34 , 45 , 51 53 ]. In the array of the ET-1R/β-arr1-integrated signaling, the RTK-activated signaling pathways have been well characterized.…”
Section: The Et-1-driven Signaling Network In Tumor Cells and Tumor‐mmentioning
confidence: 99%